PERKEMBANGAN NILAI AGAMA DAN MORAL (STTPA TERCAPAI) - Siti Nurjanah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
This study aims to determine the development of religious and moral values of early childhood in achieving STPPA and to know what can affect the development of religious and moral values of early childhood in achieving STPPA. This research is a qualitative research with analytic descriptive method. Technique of collecting data using interview then subject in this research is student of Kindergarten 'Aisyiyah Bustanul Athfal Sapen Yogyakarta with name of Siti Aisyah Khaira. The results of this study indicate that the development of religious values and moral subject has been achieved in accordance with the standards of achievement level of child development.